WET TROPOSPHERIC CORRECTION’S IMPACT ON SEA LEVEL ANOMALY AROUND THE INDONESIAN SEAS - Handoko, Eko Yuli (Departemen Teknik Geomatika ITS, 2018)
Global sea level rise in the satellite altimetry era is about 3 mm/yr. The one of main source of uncertainty of global sea level is the wet tropospheric from onboard microwave radiometer which is up to 0.3 mm/yr. The focus of this study is to assess of various wet tropospheric correction impact on sea level anomaly in the Indonesian seas. The result of sea level anomaly linear trend difference between Global Navigation Satellite System and Microwave Radio Meter or ECMWF Re-Analysis Interim is 0.18 mm/yr in agreement with the global wet tropospheric uncertainty.